Urodynamic Evaluation after High-Intensity Focused Ultrasound for Patients with Prostate Cancer - Luigi Mearini; Elisabetta Nunzi; Silvia Giovannozzi; Luca Lepri; Carolina Lolli; Antonella Giannantoni (Prostate Cancer)
This prospective study assesses the impact of high-intensity focused ultrasound (HIFU) on lower urinary tract by comparing pre- and postoperative symptoms and urodynamic changes. Thirty consecutive patients with clinically organ-confined prostate cancer underwent urodynamic study before HIFU and then at 3–6 months after surgery. Continence status and symptoms were analyzed by means of International Prostate Symptoms Score IPSS and International Index Erectile Function IIEF5. As a result, there were a significant improvement in bladder outlet, maximum flow at uroflowmetry, and reduction in postvoid residual PVR at 6-month follow-up and a concomitant significant reduction of detrusor pressure at opening and at maximum flow. De novo overactive bladder and impaired bladder compliance were detected in 10% of patients at 3 months, with progressive improvement at longer follow-up. Baseline prostate volume and length of the procedure were predictors of 6-month IPSS score and continence status. In conclusion, following HIFU detrusor overactivity, decreased bladder compliance and urge incontinence represent de novo dysfunction due to prostate and bladder neck injury during surgery. However, urodynamic study shows a progressive improvement in all storage and voiding patterns at 6-month follow-up. Patients with high prostate volume and long procedure length suffered from irritative symptoms even at long term.